Gastroesophageal Reflux, Laryngopharyngeal Reflux and Sleep Quality in Adult Population - Kargın, Maral; Dolu, İlknur; Çelebi, Evrim (My University, 2021)
Objective: This study was conducted to determine the \rinterrelationships of gastroesophageal reflux, laryngopharyngeal reflux and sleep quality in adults. Sleep quality in adults is important for \rhealth protection in terms of physiological and psychological and increasing performance. Recent studies have emphasized a strong association between sleep disorders and gastrointestinal disorders. \rMaterial and Methods: This cross-sectional study was carried out \rwith 400 individuals who are >18 years old who were registered family health centers from east, west, north, and south of Elazığ province \rbetween April and June 2018. A Personal Information Form, Gastroesophageal Reflux Disease Questionnaire, Reflux Symptom Index, \rand the Pittsburgh Sleep Quality Index were used as data collection \rtools. Results: The results of simple linear regression indicate that \rPittsburgh Sleep Quality Index global score was associated with Gastroesophageal Reflux Disease Questionnaire, Reflux Symptom Index, \rage, gender, educational status, marital status, working status, \rmonthly income perception, health perception and the person living \rtogether. By the multiple regression analysis, Reflux Symptom Index, \rGastroesophageal Reflux Disease Questionnaire, the employment status and being widow are the most correlated variables on the Pittsburgh Sleep Quality Index global score and explained 27% of the total \rvariance. Conclusion: In addition to being a significant relationship \rbetween reflux and sleep quality, it can be asserted that some sociodemographic variables besides reflux is the important parameters required while evaluating the sleep-related problems.
Keywords: Solunum Sistemi; Genel ve Dahili Tıp; Hemşirelik